Natural ressources and innovation: A new insight - Christel, Mapa Kamdoum Genevieve; Bertin, Pilag Kakeu Charles (Asian Journal of Empirical Research, 2024)
The natural resource abundance and innovation is an emerging debate, and the literature has not yet provided all the elements to refute or confirm if natural resources are cursing or blessing . This article inspects the outcome of natural resources on innovation capacity. The data came from secondary sources collected over the period 1996-2015 in a range of 58 developing and developed countries. Applying ordinary least squares regression, the result shows that (1) abundance of natural resources negatively affects innovative ability; However, considering the sorts of resources, (2) petroleum, forestry gas rent reduce the ability to innovate, while mining and coal rent increase this capacity; (3) The results also show that official development assistance not targeted at local innovation systems and poor institutional quality are mechanisms through which natural resources abundance negatively impacts innovative capacity; (4) Finally, considering heterogeneity between countries, the results also show that the natural resources abundance positively impacts the innovation capacities in low-income economies, while discouraging innovation in high-income economies. Therefore, to improve innovative capacity in resource-dependent, the governments of developed countries should direct official development assistance in developing countries to the local innovation system. In return, developing countries must improve the quality of their institutions.